They #Woke: How Black Students in an After-School Community-Based Program Manifest Critical Consciousness. Issue 1 (January 2021) - Sulé, V. Thandi; Nelson, Michelle; Williams, Tiffany
Background/Context: Though Black Americans have long suffered under racial tyranny, they have made valiant efforts to subvert policies and practices that encroach on their humanity. Nevertheless, systemic racism has been virtually unyielding—creating both racial hierarchies and disparities in access to resources and wellness. Programs designed to address the condition of Black people, particularly Black youth, often employ deficit or dysfunctional logic, thereby ignoring the sociohistorical context in which Black youth navigate. Furthermore, not enough attention is given to the ways that culturally centered approaches ignite critical consciousness among Black youth in ways that are aligned with the tradition of the Black American abolitionist mindset. Purpose: We build on the discourse on community-based youth programs and critical consciousness development by using frameworks that elevate race and culture in analyzing how Black youth make sense of their racialized experiences. Additionally, our explication challenges the overriding deficit focus of Black youth experiences within and outside school contexts by providing a nuanced view of Black youth agency. Research Design: With critical race theory as the epistemic foundation, this study sought to foreground counternarratives among youth participants of a culturally centered, community-based program. Thus, we used semistructured interviews as our primary data source. Using a three-stage analytical process, we sought to understand if and how critical consciousness manifests within this youth community. Conclusions/Recommendations: The study demonstrates the value of foregrounding African American culture and history to fortify the values of collectivism, self-determination, purpose, responsibility, empowerment, creativity, and faith among Black youth. The authors propose that educators collaborate with community-based Black culture and youth development experts to support dialogical, student-centered spaces that impart culturally centered knowledge about Black Americans. Furthermore, the authors advocate for professional development in asset-based pedagogies as a means to enhance belongingness among Black students.